The Impact of Coronavirus Disease 2019 Epidemic on Dizziness/Vertigo Outpatients in a Neurological Clinic in China - Li, Changqing; Guo, Dongsheng; Ma, Xiangke; Liu, Siwei; Liu, Mingyong; Zhou, Lichun (Frontiers in Neurology, 2021)
Objective: This study aims to investigate the impact of the coronavirus disease 2019 (COVID-19) epidemic on dizziness/vertigo outpatients in a neurological clinic in China. Methods: Against the background of the COVID-19 epidemic, the data of patients who visited the neurological clinic of Beijing Chaoyang Hospital West Branch during the pandemic (February 1–May 30, 2020) and the corresponding period in 2019 (February 1–May 30, 2019) were analyzed, and patients with dizziness/vertigo from these two periods were compared to discover their demographic features and etiologic distribution according to their age and sex. Result: The absolute number of neurological outpatients decreased from 14,670 in 2019 to 8,763 in 2020 (−40.3%), with a corresponding decline in dizziness/vertigo patients (2019: n = 856; 2020: n = 1,436, −40.4%). Dizziness/vertigo was more common in women than men in these two periods (2019: women = 63.6%; 2020: women = 63.1%, p = 0.82). The overall etiology distribution was different among all disorders between the two periods (p < 0.001). There was an increase in benign paroxysmal positional vertigo (BPPV) (2019 vs. 2020: 30.7 vs. 35%, p < 0.05) and psychogenic/persistent postural perceptual dizziness (PPPD) (2019 vs. 2020: 28.5 vs. 34.6%, p < 0.05) while a decrease in vascular vertigo during the epidemic (2019 vs. 2020: 13 vs. 9.6%, p < 0.05). During the epidemic, the top three causes of dizziness/vertigo were BPPV (35%), psychogenic/PPPD (34.6%), and vascular vertigo (9.6%). A female predominance was observed in BPPV (women = 67.7%, p < 0.05) and psychogenic/PPPD (women = 67.6%, p < 0.05). In addition, the etiology ratio of different age groups was significantly different (p < 0.001). The most common cause for young and young-old patients was BPPV, and the most common cause for middle-aged and old-old patients was psychogenic/PPPD. Conclusion: The absolute number of outpatients with dizziness/vertigo during the COVID-19 pandemic was reduced during the early period of the COVID-19 outbreak. BPPV and psychogenic/PPPD were more abundant, and vascular vertigo was less frequent. Based on those data, health-care management policy for dizziness/vertigo and mental disorder should be developed during the outbreak of COVID-19 and other infective diseases.